1997
DOI: 10.1093/nar/25.2.297
|View full text |Cite
|
Sign up to set email alerts
|

The SV40 large T-antigen helicase can unwind four stranded DNA structures linked by G-quartets

Abstract: We describe a novel activity of the SV40 large T-ag helicase, the unwinding of four stranded DNA structures linked by stacked G-quartets, namely stacked groups of four guanine bases bound by Hoogsteen hydrogen bonds. The structures unwound by the helicase were of two types: (i) quadruplexes comprising four parallel strands that were generated by annealing oligonucleotides including clustered G residues in a buffer containing Na+ions. Each parallel quadruplex consisted of four oligonucleotide molecules. (ii) Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…This result is compatible with a previous observation that formation of a Watson-Crick base pair between residue N5 in the primer and residue A51 in the RNA template is less essential for the extension reaction than formation of a base pair between residue N4 in the primer and A50 in the template (19). Figure 4B shows interference footprinting assays performed with this oligonucleotide, using formic acid and KMnO 4 . It can be seen that modifications of residues G2, G3, and A5 strongly interfered with the extension of the primer, whereas the interference due to modifications of residues G6 and G7 was more moderate.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is compatible with a previous observation that formation of a Watson-Crick base pair between residue N5 in the primer and residue A51 in the RNA template is less essential for the extension reaction than formation of a base pair between residue N4 in the primer and A50 in the template (19). Figure 4B shows interference footprinting assays performed with this oligonucleotide, using formic acid and KMnO 4 . It can be seen that modifications of residues G2, G3, and A5 strongly interfered with the extension of the primer, whereas the interference due to modifications of residues G6 and G7 was more moderate.…”
Section: Resultssupporting
confidence: 91%
“…Inspection of the KMnO 4 footprint of oligo tel3 reveals that the interference caused by modification of residue T4 was much less substantial than that observed in the KMnO 4 footprint of oligo tel1. A similar observation was made in a KMnO 4 footprinting assay of an additional variant of oligo tel1 in which residue T5 was deleted (not shown). Apparently, the absence of T5 affected the interactions of these primers with the enzyme so that the role of T4 in the reaction became less significant.…”
Section: Resultssupporting
confidence: 78%
“…Therefore, we investigated the effects of GRO29A on the replication-associated proteins most likely to be modulated. These were the SV40 large T antigen, which is known to bind to and unwind G-quartet structures (42), and RPA, which is known to bind to nucleolin (20), the putative GRO-binding protein (9). Although we could observe the interaction between nucleolin and RPA, we found that this was not significantly affected by the presence of GROs.…”
Section: Discussionmentioning
confidence: 62%
“…The ability of T antigen to unwind structures containing G-quartets has been documented previously (42); therefore, we postulated that the presence of an excess of G-quartet containing oligonucleotide could sequester the helicase activity and prevent template unwinding and replication. To test this hypothesis we carried out T antigen helicase assays in the presence of various oligonucleotides.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation